(untitled) (Universal International Scientific Journal, 2026)
This article uses a transnational approach to analyze the cultural identity and everyday life strategies of Uzbek migrants living in the Republic of Korea in the context of labor, educational, and marriage migration. It also examines Uzbek migrants’ labor relations, strategies for social mobility through education, changes in gender and family relations within marriage migration, and the impact of language, religion, and everyday practices on cultural identity.